Exclusive endocrine therapy or partial breast irradiation for women aged ≥70 years with luminal A-like early stage breast cancer (NCT04134598 – EUROPA): Proof of concept of a randomized controlled trial comparing health related quality of life by patient reported outcome measures. Issue 2 (March 2021) - Meattini, Icro; Poortmans, Philip M.P.; Marrazzo, Livia; Desideri, Isacco; Brain, Etienne; Hamaker, Marije; Lambertini, Matteo; Miccinesi, Guido; Russell, Nicola; Saieva, Calogero; Strnad, Vratislav; Visani, Luca; et al.
Abstract: Background: Postoperative radiation therapy after breast conserving surgery in the older adult population is a matter of debate; although radiation therapy was shown to benefit these patients concerning local disease control, the absolute benefit was small and potentially negligible. Partial breast irradiation has been introduced as an alternative treatment approach for low-risk patients. Older adult patients with early breast cancer constitute a unique population with regards to prognosis and potential comorbidities, thus minimizing treatment to maintain health-related quality of life (HRQoL) without compromising survival is extremely important. Estimates of the patient's risk of benefit and/or harm with treatment should be performed together with an assessment of baseline comorbidities, life expectancy, and care preferences. Published data suggest that radiation therapy or endocrine therapy alone resulted in excellent disease control in older women with early breast cancer, and that the combination of both treatments has less incremental benefit than expected. Conversely, the toxicity profile of endocrine therapy is well known, often significantly impacting long term HRQoL of these potentially frail patients. Methods: Patients older than 70  years receiving breast conserving surgery with T1N0, Luminal A-like tumors will be randomized to receive partial breast irradiation-alone or endocrine therapy-alone. The main objectives are to determine patient reported outcome measures in terms of HRQoL, as assessed by the EORTC QLQ-C30 using the global health status of patients, and to demonstrate a non-inferior local control rate between arms. Secondary endpoints are represented by individual scales from QLQ-C30 and module QLQ-BR45 scores; ELD14 questionnaire; geriatric COre DatasEt assessment; distant control rate, adverse events rates, breast cancer specific, and overall survival. Discussion: The EUROPA trial is a new randomized trial focused on older adults (≥70  years) affected by good prognosis primary breast cancer. Our assumption is that postoperative radiation therapy-alone avoids the long-term toxicity of endocrine therapy and favorably impacts on HRQoL in this population. In the current report we present the trial's background and methods, focusing on perspectives in the field of precision medicine. Trial registration : The trial is registered with ClinicalTrial.gov Identifier NCT04134598 / EUROPA trial.